1995
DOI: 10.1093/rheumatology/34.3.232
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Clonality in Synovial Fluid From Rheumatoid Joints Before and After Culture in Interleukin-2

Abstract: T-cell receptor (TCR) gamma gene rearrangements which have been amplified in polymerase chain reactions (PCRs) and analysed by high resolution polyacrylamide gel electrophoresis have been used to investigate the clonal diversity of T-cells in joint effusions from 16 patients with rheumatoid arthritis, one with systemic lupus erythematosus and one with psoriatic arthropathy. Polyclonality was found in every case but an oligoclonal subset of dominant rearrangements was also demonstrated in all but the patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…To date, TCRBV clonality studies in RA have yielded conflicting results. In some studies evidence of oligoclonality of SF T cells has been demonstrated [48–50], but in other studies no evidence of oligoclonality was found [51–53]. We have found three clonally expanded TCRBV subsets in the SF in each patient studied, with two of them (BV13·1/3 and BV22) being shared by the two patients.…”
Section: Discussionmentioning
confidence: 52%
“…To date, TCRBV clonality studies in RA have yielded conflicting results. In some studies evidence of oligoclonality of SF T cells has been demonstrated [48–50], but in other studies no evidence of oligoclonality was found [51–53]. We have found three clonally expanded TCRBV subsets in the SF in each patient studied, with two of them (BV13·1/3 and BV22) being shared by the two patients.…”
Section: Discussionmentioning
confidence: 52%
“…V ␤ 7 cells were usually not prominent in these studies, in which PCR primers were used to specifically detect the BV7 transcripts (a method that should detect all 3 BV7 genes but does not distinguish between the 3 different BV7 genes). In one study (52) using samples from Japanese patients with primary SS or with human T lymphotropic virus type I-associated SS, BV7 transcripts were elevated and clonally restricted. A conserved third complementarity-determining region motif (QDXG) was noted among these BV7 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,12 As such, the finding of an (oligo)clonal T-cell population in the synovial tissue of patients with RA or other inflammatory rheumatic diseases even in absence of a T-cell malignancy can occur. [20][21][22] Tachibana et al 12 reported the detection of an identical clone in synovial fluid and LN by SB analysis in a patient with T-zone lymphoma. However, up until now no primary skin lesions of patients with MF have been analyzed for direct comparison.…”
Section: Discussionmentioning
confidence: 99%